2012
DOI: 10.3148/73.2.2012.59
|View full text |Cite
|
Sign up to set email alerts
|

Role of a Food Box Program: In Fruit and Vegetable Consumption and Food Security

Abstract: Participation in a food box program can provide some benefit in terms of increased fruit and vegetable consumption for those who use the program regularly. Increasing the frequency of the box and encouraging continued use may improve these effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 26 publications
1
27
0
Order By: Relevance
“…They also more often consumed some summer vegetables and fruits when locally in-season than when out-of-season. Our findings are consistent with prior studies that found adult CSA members consumed a larger quantity of fruits and vegetables than their non-CSA counterparts [ 27 , 37 , 38 , 39 , 40 , 41 ], and add important evidence that children in CO-CSA households also have higher FVI. Furthermore, all households in our sample had low incomes, and more than half were food insecure, which are circumstances known to increase risk for inadequate FVI [ 10 , 11 , 12 , 14 , 15 , 16 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…They also more often consumed some summer vegetables and fruits when locally in-season than when out-of-season. Our findings are consistent with prior studies that found adult CSA members consumed a larger quantity of fruits and vegetables than their non-CSA counterparts [ 27 , 37 , 38 , 39 , 40 , 41 ], and add important evidence that children in CO-CSA households also have higher FVI. Furthermore, all households in our sample had low incomes, and more than half were food insecure, which are circumstances known to increase risk for inadequate FVI [ 10 , 11 , 12 , 14 , 15 , 16 ].…”
Section: Discussionsupporting
confidence: 92%
“…CSAs can improve access to fresh produce because they are located within the communities they serve [ 27 , 35 ], and often provide higher quality produce at a lower price than grocery stores [ 23 , 28 , 36 ]. In cross-sectional surveys, CSA members commonly report consuming a larger quantity and broader variety of vegetables after joining a CSA [ 27 , 37 , 38 ], and longitudinal studies suggest some impact of CSAs on at least some measures of FVI [ 32 , 39 , 40 , 41 ]. However, most current CSA members are from middle- to high-income households [ 28 , 36 , 42 , 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…Program participation was associated with improved intake of vegetables. [57] A home delivered meals program for elderly participants was effective in reducing food insecurity and improving nutritional status. [58]…”
Section: Nutrition Support Interventionsmentioning
confidence: 99%
“…Although this research did not evaluate food access outcomes, non-significant or unclear reductions in food insecurity were associated with the use of a similar box scheme in Canada. 6 Nonetheless, participant engagement and retention were once again suggested to be pivotal to achieve these outcomes. 6 When implementing community initiatives, the process of engaging community members and addressing each of these factors should not be overlooked.…”
Section: Major Themes Subthemesmentioning
confidence: 99%
“…6 Nonetheless, participant engagement and retention were once again suggested to be pivotal to achieve these outcomes. 6 When implementing community initiatives, the process of engaging community members and addressing each of these factors should not be overlooked.…”
Section: Major Themes Subthemesmentioning
confidence: 99%